2016
DOI: 10.3390/su8111177
|View full text |Cite
|
Sign up to set email alerts
|

Grassland and Wheat Loss Affected by Corn and Soybean Expansion in the Midwest Corn Belt Region, 2006–2013

Abstract: Increases in agricultural commodity price triggered by ethanol production and other socioeconomic conditions have dramatically affected land uses and agronomic practices in the U.S. This study used crop-specific land cover data from the U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the effect of DESs on some of the rarely studied, yet biologically important proteins or enzymes has been included in this section. The proteins or enzymes which have been covered here are, collagen, [148][149][150][151] keratin, [152][153][154][155] subtilisin, 112 chondroitinase ABCI (cABCI), 156 chicken villin headpiece subdomain (HP 36), 157 human interferon-a2 (IFN), 158 b-glucosidase, 159 b-lactamase, 160 transferrin, 161 bovine ribonuclease A (RNase A), 42 b-galactosidase, 162 papain, 163 pepsin, 164 Trp-cage mini protein 165 and bromelain. 30 Collagen is the most abundant protein, being an essential constituent of the extracellular matrix of living beings.…”
Section: The Structural Stability and Activity On Other Proteins In Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of DESs on some of the rarely studied, yet biologically important proteins or enzymes has been included in this section. The proteins or enzymes which have been covered here are, collagen, [148][149][150][151] keratin, [152][153][154][155] subtilisin, 112 chondroitinase ABCI (cABCI), 156 chicken villin headpiece subdomain (HP 36), 157 human interferon-a2 (IFN), 158 b-glucosidase, 159 b-lactamase, 160 transferrin, 161 bovine ribonuclease A (RNase A), 42 b-galactosidase, 162 papain, 163 pepsin, 164 Trp-cage mini protein 165 and bromelain. 30 Collagen is the most abundant protein, being an essential constituent of the extracellular matrix of living beings.…”
Section: The Structural Stability and Activity On Other Proteins In Dessmentioning
confidence: 99%
“…It was suggested that enzyme activation is dependent on the presence of both the anion and HBD in the DES. Recently, research work by Lin et al 163 demonstrated papain immobilization on ChCl–lactic acid DES-treated chitosan exhibiting tremendous thermostability compared to the free enzyme. This thermal stability of the immobilized enzyme is provided by hydrogen-bonding interactions between the enzyme, chitosan, and residual DES, which are beneficial for maintaining an active conformation and subsequently high thermal stability for the enzyme.…”
Section: The Structural Stability and Activity On Other Proteins In Dessmentioning
confidence: 99%